Enhancement of ammonia gas sensitivity and selectivity by depleted layer of PBTTT-C14/MoS2-QDs heterojunction based thin film transistor - Gupta S.; Pal B.N.; Prakash R. (My University, 2025)
A highly sensitive, room temperature operating ammonia (NH3) gas sensor has been fabricated by using PBTTT-C14/MoS2-QDs heterojunction based organic thin film transistor (OTFT). Thin film of PBTTT-C14/MoS2-QDs has been fabricated by low cost and high yield ‘floating film transfer method’ (FTM). Initially, hydrothermally synthesized MoS2 quantum dots (QDs) were added in PBTTT-C14 polymer to make a composite ink, which was used for film fabrication. This polymer/QDs based film has been used as a channel of a top contact-bottom gated organic thin film transistor. Various concentration of NH3 ranging from 0.5 to 50 ppm has been exposed on the channel to determine the sensitivity and the selectivity of the device. For comparison, a reference OTFT has been fabricated under the same condition by using pristine PBTTT-C14 thin film. It has been observed that the response of the polymer/QDs heterojunction device is ∼ 85 % at 50 ppm which is ∼ 3 times higher compared to reference device in higher concentration range of NH3. This enhancement becomes possible due to the NH3 sensitive depletion layer of polymer/QDs heterojunction. This OTFT sensor shows high selectivity to the NH3 gas with good linearity to the concentration, which can fulfill basic requirements for practical utilization. © 2023 Elsevier B.V.